HUBUNGAN IMT DENGAN KADAR GULA DARAH PADA LANSIA DI POSYANDU SABAR NARIMO DUSUN LEMPUYANGAN DESA GEBUGAN KECAMATAN BERGAS KABUPATEN SEMARANG: CORRELATION OF BMI WITH BLOOD SUGAR LEVELS IN THE ELDERLY AT POSYANDU SABAR NARIMO DUSUN LEMPUYANGAN, GEBUGAN VILLAGE, BERGAS DISTRICT, SEMARANG REGENCY - Kodir Kodir; Margiyati Margiyati; Shania Nada; Rani Pratiwi (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2019)
The increase in Life Expectancy (UHH) has an impact on the increase in the elderly population and the problems due to aging. One of them is the system for regulating blood sugar levels which is disrupted due to changes in the body composition of the elderly in the form of increased fat composition from the body 14% to 30%. Efforts to prevent the incidence of Diabetes Mellitus is to achieve good nutritional status with anthropometric measurements, namely the division of body weight in kg with height in meters squared expressed in body mass index or BMI. This study aims to analyze the relationship between BMI and blood sugar levels in the elderly at the Sabar Narimo Posyandu, Lempuyangan Hamlet, Gebugan Village, Bergas District, Semarang Regency. The research design used was descriptive observational with a cross sectional approach. The number of samples was 40 elderly who were taken by purposive sampling technique. The instrument used to measure BMI is a digital weight scale, and a microtoise that has been calibrated, while blood sugar levels are measured using a glucometer. Data were analyzed by Pearson Corellation test. The results of this study indicate the frequency distribution of blood sugar levels in the elderly at the Posyandu Sabar Narimo on average 139.92 mg/dl and an average BMI of 25.24 kg/m2. The results showed that BMI was related to the variable of blood sugar levels with a correlation coefficient (r) of 0.614 and a significance value (?) of 0.0234 then there is a relationship. The conclusion in this study is that there is a relationship between blood sugar and BMI in the elderly at the Sabar Narimo Posyandu, Lempuyangan Hamlet, Gebugan Village, Bergas District, Semarang Regency.